S. S. ALEKSEYEV’S LEGAL CONCEPTION IN THE CONTEXT OF WESTERN LEGAL POSITIVISM OF THE SECOND HALF OF THE XX – EARLY XXI CENTURY: SYSTEMATICITY OF LAW, LEGAL NORM AND LAW-ENFORCEMENT IN SITUATIONS OF INDETERMINACY (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article discusses the classical views of the outstanding Russian jurist Sergey Sergeyevich Alekseyev in the context of the basic examples of foreign legal positivism of the second half of the XX century and further (H. Kelsen, H. Hart, J. Raz, C. Alchourron, E. Bulygin, etc.). The subject-matter of the analysis, in addition to the characteristics of positivistic theory, are the issues of understanding and constructing legal norms as elements of legal system, as well as issues of their application in situations of legal gaps and conflicts.
Keywords: Alekseev Sergey Sergeevich; legal positivism; systematicity of law; legal norm; law-enforcement; legal gap; legal conflict